IMPLEMENTASI KELAS RAMAH KEGAGALAN UNTUK MENINGKATKAN GROWTH MINDSET SISWA MELALUI EVALUASI ULANG KESALAHAN DALAM UJIAN - Mufidah, Maria; Azizi, Faiz; Siraj, A. Yusril Hasani; Fajri, Ach Nurfuad (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of failure-friendly classrooms as a learning strategy to foster a growth mindset in elementary school students. In an educational context that still emphasizes final grades as an indicator of success, this approach offers a new paradigm that makes mistakes a crucial part of the learning process. Through re-evaluation of exam errors, students are encouraged to reflect, correct, and constructively understand their mistakes. This study used a qualitative method with a case study design at PP. Bustanul Ulum Mlokorejo, involving teachers and students as key informants. The results indicate that this approach can improve students' self-confidence, learning motivation, and self-regulation skills. Teachers act not only as assessors but also as facilitators who accompany the reflection process. Despite challenges such as time constraints, this strategy has been proven to create a more inclusive, supportive, and humanistic learning environment. These findings align with the theories of growth mindset (Dweck), self-efficacy (Bandura), and reflective learning (Brookhart), and support the vision of the Independent Curriculum (Kurikulum Merdeka), which places students as active subjects in learning. This study recommends the wider adoption of failure-friendly classrooms as part of transformative elementary education reform.